(untitled) - Genuchten, M. Th.van (Mexico, 1994)
The focus of soil physics research, and that of soil science in general, has gradually broadened from mostly agricultural production issues to more comprehensive studies of subsurface water flow and chemical transport geared toward environmental issues. There is an abundance of ongoing and new challenges in soil physics research, notably in the areas of subsurface heterogeneity (including preferential flow), multiphase flow, multicomponent transport, and hydraulic property characterization. Soil heterogeneity at a variety of spatial scales remains a frustrating problem affecting the measurement, prediction, and management of subsurface flow and transport processes. More realistic deterministic and stochastic models, as well as improved sampling methods and instrumental techniques, are slowly becoming available to make the research more effective. Several examples are given to illustrate soil physics contributions to the solution of agricultural and environmental problems.
Keywords: Soil physics,Vật lý đất